PARADIGMA PENYELESAIAN SENGKETA BISNIS EKONOMI SYARI'AH MELALUI LEMBAGA LITIGASI DAN NON LITIGASI - Arif Hariyanto (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2013)
The Birth of Law No. 3 of 2006 Amendments Act No. 7 of 1989 On the Religious has brought major changes in the existence of the Religious institutions today.One fundamental change is the addition of the Religious authority agency (PA) in theeconomic field Shariah. Pursuant to Article 49 letter (i) of Act No. 3 of 2006 affirmed that the religious court has authority to examine, hear and resolve the case "Sharia Economy".The authority in the Shari'a judge, the role of the Religious will grow wider. Because of Shariah-related economic discipline of economics, so that the judges in the Court of Religion should master of science in economics in addition to Shariah law formally owned over the years. It is very reasonable because when the Act was implemented within the religious court judges still do not understand and know the economic law of sharia.Therefore shariah economy business dispute settlement no longer mentions the District Court (PN) as a place of dispute settlement in the shari'ah business. In this case the financial institution Bank and Non Bank to change the contract clause of the contract-financing by shariah bank so far. So that the provisions in the economic case can be settled by sharia religious court and no longer BASYARNAS District Court for execution.